An international investigation of the Austrian theory of the business cycle - Tsionas, Efthymios; Kollintzas, Tryphon; Konstantakopoulou, loanna (SPOUDAI Journal of Economics and Business, 2009)
In this paper we investigate the validity of the Austrian theory of business cycle. We use international data that span 1980-2005 and we utilize the available information in the most efficient manner via unit panel root and panel cointegration analysis. The relationships among the variables of the Austrian theory of business cycle are investigated using cointegrating techniques. Our results are in favour of the Austrian theory. JEL Classifications: E32, E51